“Seeing is Believing:” Research project on smartphone camera data for agricultural risk management - Kannan, Samyuktha; Kramer, Berber; Singh, Vartika (International Food Policy Research Institute, 2019)
IFPRI, together with partners from India as well as the academic community, pioneered in testing whether smartphone camera data could strengthen insurance products in India. A proof of concept study of “picture-based insurance” (PBI), an easy-to-understand low-cost insurance product for visible crop damage, was conducted between 2016 and 2018 in Punjab and Haryana on the wheat crop. Along with technical and implementation partners including HDFC, we also leveraged smartphone camera data to provide personalized agricultural advice based on real-time observations of crop conditions, from sowing to harvest. Through a randomized trial we found that “picture-based insurance” overcomes limitations of traditional insurance products and that there is a strong case for bundling the insurance with other customized risk-reducing services such as advisories. To build on this research further and develop a sustainable and scalable risk-management solution, the project won the Inspire Challenge Scale-up Grant in 2018 awarded by the CGIAR Big Data Platform.